2017 Global Hunger Index: The inequalities of hunger - von Grebmer, Klaus; Bernstein, Jill; Hossain, Naomi; Brown, Tracy; Prasai, Nilam; Yohannes, Yisehac; Patterson, Fraser; Sonntag, Andrea; Zimmerman, Sophia-Maria; Towey, Olive; Foley, Connell (International Food Policy Research Institute, 2017)
The 2017 Global Hunger Index (GHI) shows long-term progress in reducing hunger in the world. The advances have been uneven, however, with millions of people still experiencing chronic hunger and many places suffering acute food crises and even famine. According to 2017 GHI scores, the level of hunger in the world has decreased by 27 percent from the 2000 level. Of the 119 countries assessed in this year’s report, one falls in the extremely alarming range on the GHI Severity Scale; 7 fall in the alarming range; 44 in the serious range; and 24 in the moderate range. Only 43 countries have scores in the low range. In addition, 9 of the 13 countries that lack sufficient data for calculating 2017 GHI score << - including Somalia, South Sudan, and Syria - raise >> significant concern, and in fact may have some of the highest levels of hunger.